การตรวจสอบแบบจำลองการลดทอนคลื่นด้วยสมการทำนายการเคลื่อนที่พื้นดินของ NGA West-2 ในพื้นที่ลุ่มสามเหลี่ยมปากแม่น้ำอิระวดี ประเทศเมียนมาร์ - Oo, Yaung Ni Paw; Tanapalungkorn, Weeradetch; Likitlersuang, Suched (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
The Ayeyarwady Delta Basin is classified as a moderate seismic zone, bounded by the Kabaw and Sagaing Faults. The significant impacts of past earthquakes have been exacerbated by the region’s population density and economic development. Consequently, numerous studies have been conducted in this area, particularly in Yangon. However, the lack of a suitable attenuation model tailored to the region remains a critical issue, especially in the absence of robust ground motion data. This study aims to identify the most appropriate ground motion model by evaluating four attenuation models included in the NGA West-2 GMPEs for shallow crustal earthquakes in active tectonic regimes. The Peak Ground Acceleration (PGA) and Spectral Acceleration (SA) of 28 seismic events are predicted using these models. Ground motion data from these events, collected from eight broadband seismic stations in Myanmar, are used to verify each attenuation model. The most suitable model is determined through a best-fit test and optimization techniques applied to the observed and predicted ground motion data. The findings reveal that the BSSA14 model from NGA West-2 is the most appropriate for the study area. These results provide a valuable contribution to future seismic studies and hazard preparedness efforts by enabling the selection of a more accurate and region-specific attenuation model.